Breast cancer screening in low and middle-income countries. (September 2022) - Newman, Lisa A.
Abstract: Breast cancer incidence rates are rising in low and middle-income countries (LMIC), and these populations have reduced access to advanced multidisciplinary treatment. Screening and early detection are therefore critical in these regions but must be affordable and sustainable. Mammography screening programs are well established in more affluent countries, but alternative strategies to reduce the breast cancer burden of LMIC (such as clinical breast examination, general breast health awareness, and addressing modifiable lifestyle factors including obesity) are likely to be more realistic at the present time.